Digital Communication in the Formation of Teen Character: An Analysis of the Facebook Account 'Amperaku' in Ampera Village - Ibrahim, Almunawar; Muhammad, Burhanudin A.; Hasim, Iksan; Jailan, Putri Nurdiana (Peneliti.net, 2025)
This study aims to analyze digital communication on the character formation of adolescents in Ampera Village and identify social and moral values that develop through digital interactions. The research method used is qualitative with a descriptive type/approach, aiming to analyze digital communication on the character formation of adolescents in Ampera Village and identify social and moral values that develop through digital interactions. This study found that digital communication in the Facebook account